Treatment of Auricular Pseudocyst with Intralesional Steroid: A Study with Short-Term Follow-Up - Parajuli R; Kshetry J (Dove Medical Press, 2020)
Ramesh Parajuli,1 Jiwan Kshetry2 1Department of ENT, Chitwan Medical College, Bharatpur, Nepal; 2Department of Pathology, Narayani Samudayik Hospital, Bharatpur, NepalCorrespondence: Ramesh ParajuliDepartment of ENT, Chitwan Medical College, P.O. Box 42, Bharatpur 10, NepalTel +977-56532933Email drrameshparajuli@gmail.comIntroduction: A pseudocyst is an uncommon, painless, benign cystic swelling on the lateral surface of the auricle with an unknown etiology. Various treatment modalities have been used with varying rates of success as this condition has high propensity for recurrence. We have used a minimally invasive treatment method for this condition to evaluate its efficacy in our setup.Patients and Methods: This is a prospective study carried out in the department of ENT of Chitwan Medical College from May 2018 to April 2020. Complete aspiration of the pseudocyst with intralesional steroid (40 mg, triamcinolone acetonide) injection was done in 30 patients. They were followed up weekly for 4 weeks. Additional doses were injected in cases with persistence or recurrenqce before 3 weeks. Disappearance of the swelling, considered treatment success, was the main outcome. The total number of doses required for the complete resolution of the swelling along with the number of recurrences or complications, if any, were noted at the final follow-up at 4 weeks.Results: All of our patients responded completely with intralesional triamcinolone. However, the total dose requirement for different patients varied. Out of the 30 patients, 21 (70%) responded to the single dose of the drug. Six (20%) required a second dose, while the remaining 3 (10%) patients required a third dose for complete resolution of the swelling. All three (10%) patients who received a third dose of triamcinolone complained of skin thickening, but there was no obvious cosmetic deformity.Conclusion: Aspiration with intralesional steroid injection shows an immediate positive response in patients with auricular pseudocyst. It can achieve complete resolution of the swelling without any serious complications. Thus, it appears to be a simple and effective management of the condition in the short term.Keywords: pseudocyst, pinna, intralesional, triamcinolone